Early career retention in consulting firms within Botswana. - Shukla, Shuchita (My University, 2017)
Financial consulting firms rely heavily on the scarce skills of their workers. These individuals possess scare skills and bring forth innovate concepts that provide firms with a strong competitive market advantage. Therefore, firms are sensitive to the movement of their top talent, making effective retention strategies a vital component of their business model. This study was conducted for the purposes of understanding effective retention strategies for early career professionals working in financial consulting firms in Botswana. A thorough review of existing literature related to management and retention theories was conducted to establish relevant and effective strategies firms used within the strategic Human Resources (HR) framework. The results of the qualitative research study were based on twelve (12) semi-structured interviews which took place in January (2017). Content analysis was used to analyse the responses received during the interviews. Thereafter outcomes were ranked based on the most frequent and supported responses amongst the interviewees. The results suggest that the early career professionals in the financial consulting field place more importance on factors that are ‘Motivators’ or provided long-term growth and achievements such as development, recognition and responsibility. While extrinsic factors such as higher remuneration are rated lower as factors leading to retention, even though other studies have suggested that early career professionals are driven mainly by financial gain. In addition, the results also highlight diversity, both cultural and skill, as a factor that talent considered when deciding whether to continue working in the organisation. Respondents found cultural and ethnic diversity to enhance productivity, create of new attitudes, skills, understanding and processes. Whilst skills diversity was said to influence the retention decisions as it enabled people to rely on the different strengths of one another, making the workplace more collaborative. Few of the recommendations highlighted include allowing employees to structure their own performance goals and the process needed in achieving them, alongside dealing with management’s lag as an obstruction in achieving these goals.
MBA Thesis
Keywords: Employee retention -- Botswana,Personnel management -- Botswana.